Synthesis, Structural and Antibacterial Studies of Some Ni(II) and Cu(II) Macrocyclic Complexes - Ambwani, Jitendra; Bansal, N.L.; Rani Sharma, Mamta; Ksushik, Kshama (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes of formulae M(DPODH) (OAc)2, (Where M = Ni(II) and Cu(II) and (DPODH)(OAc)2 = 2,6- diacetyl pyridine oxy diacetic acid dihydrazone have been synthesized and characterized with the help of elemental studies, IR spectral analysis and electronic spectra. These have been further screened antimicrobially for their biological studies against bacterial species E. coli (gram negative) and S. aureus (gram positive) and fungi C. albicans and found to posses greater biological effect as compared to the ligand fragments and the metal salts.